Increasing Student’s Speaking Ability Through Series of Picture Technique for the Seventh Graders of Mts Nw 02 Rensing in the School Year 2022/2023: A Study of Students with Low Speaking Performances - Safari, M. Ubaidillah Karomi (International Conference on Islamic Studies, 2022)
This study focused on teaching speaking through a series of pictures technique. Problems were (1) To what extent attainment of teaching speaking through series of picture technique?. (2) To what extent the effect of using series of picture technique in teaching speaking to increase students’ speaking ability?. This was an experimental study. It consisted of two groups by 40 students divided into 20 students as experimental and 20 as control group. I used speaking test in series of picture and hypothesis testing. Result showed that in pre-test students as experimental group had lowest score was 33 and highest was 69 while in post-test they obtained the lowest score 57 and highest was 84. Besides, in control group the lowest score was 31 and highest score was 49 while in post-test lowest score was 43 and the highest score was 65. Mean score obtained by experimental group in pre-test and post-test were 47.8 and 67 with standard deviation were 8.71 and 7.394. Mean score obtained by control group in pre-test and post-test were 6.629 and 5.244. Thus, t-test was higher than t-table which mean teaching speaking through series of picture could increase students’ speaking ability. Hypothesis was accepted and null hypothesis was rejected.